Assessment of agricultural associativity business, among farm producers victims of the armed conflict in Samaná – Caldas - Herrera Castañeda, José Mauricio
The town of Samaná in the department of Caldas, shows a historical low level of development, revealed in its high rates of poverty; in addition, the occurrence of armed groups caused the displacement of more than twenty thousand (20,000) countrymen from 2003 to 2007, a situation that deepened the economic backwardness of the municipality. In this context, during the last six (6) years, the strengthening and creation of rural associative groups seeking to improve the negotiating capability has been promoted, the manner of articulation and integration of the rural population to the agricultural markets, through: (i) the technical and organizational qualification, (ii) the promotion and management of programmes such as Rural Opportunities, Productive Partnerships, DPS entrepreneurship programmes, etc., and  (iii) the targeting of rural development incentives to favouring  projects under partnership schemes.  The aim of the research project exhibited in this article was to assess the impact of different processes and implemented programs, into the improvement of productive, administrative processes and socio-economic conditions of the countrymen. A comprehensive diagnostic tool was implemented, focused onto a sample of eight (8) associative groups. The results showed that the implementation of such projects, have a positive impact on business processes, team work, self-saving and solidarity among group members. Similarly, the company's view of the rural microenterprises of the municipality has changed substantially. Company's vision of rural microenterprises of the municipality has also changed substantially.